Changes in Oviductal Cells and Small Extracellular Vesicles miRNAs in Pregnant Cows - Mazzarella, Rosane; Bastos, Natália Marins; Bridi, Alessandra; del Collado, Maite; Andrade, Gabriella Mamede; Pinzon, Jorge; Prado, Cibele Maria; Silva, Luciano Andrade; Meirelles, Flávio Vieira; Pugliesi, Guilherme; Perecin, Felipe; da Silveira, Juliano Coelho (Frontiers in Veterinary Science, 2021)
Early embryonic development occurs in the oviduct, where an ideal microenvironment is provided by the epithelial cells and by the oviductal fluid produced by these cells. The oviductal fluid contains small extracellular vesicles (sEVs), which through their contents, including microRNAs (miRNAs), can ensure proper cell communication between the mother and the embryo. However, little is known about the modulation of miRNAs within oviductal epithelial cells (OECs) and sEVs from the oviductal fluid in pregnant cows. In this study, we evaluate the miRNAs profile in sEVs from the oviductal flushing (OF-sEVs) and OECs from pregnant cows compared to non-pregnant, at 120 hours after ovulation induction. In OF-sEVs, 8 miRNAs (bta-miR-126-5p, bta-miR-129, bta-miR-140, bta-miR-188, bta-miR-219, bta-miR-345-3p, bta-miR-4523 and bta-miR-760-3p) were up-regulated in pregnant and one miRNA (bta-miR-331-5p) was up-regulated in non-pregnant cows. In OECs, 6 miRNAs (bta-miR-133b, bta-miR-205, bta-miR-584, bta-miR-551a, bta-miR-1193 and bta-miR-1225-3p) were up-regulated in non-pregnant and none was up-regulated in pregnant cows. Our results suggest that embryonic maternal communication mediated by sEVs initiates in the oviduct, and the passage of gametes and the embryo presence modulate miRNAs contents of sEVs and OECs. Furthermore, we demonstrated the transcriptional levels modulation of selected genes in OECs in pregnant cows. Therefore, the embryonic-maternal crosstalk potentially begins during early embryonic development in the oviduct through the modulation of miRNAs in OECs and sEVs in pregnant cows.